Concrete durability and repair technology proceedings of the International Conference held at the University of Dundee, Scotland, UK on 8-10 September 1999 - Dhir, Ravindra K.; McCarthy, Michael J. 1965- (Creating with concrete., 1999)
This text covers recent developments in the areas of durability provisions, assessment and monitoring, and repairs. Specific topics discussed include, selection of materials and mix composition, performance specification and durability by intent.